LINGUISTIC DIFFERENCES BETWEEN BRITISH AND AMERICAN ENGLISH - Ibayev Anvar Jurabekovich; Aktamova Dilnoza Bozorboy qizi; Zokirova Sevinch Quvonchbek qizi; Beknazarova Dinara Matlubjon qizi; Boliqulova Muxlisa Nomoz qizi; Ismatullayeva Bahora G'aybulla qizi (TADQIQOTLAR, 2026)
Abstract: This article investigates the primary linguistic distinctions between British English and American English, concentrating on phonetic, lexical, grammatical, orthographic, and pragmatic dimensions. Both varieties come from the same historical source, but they have grown apart because of where they are, the cultures they are in, and how they have evolved as languages. The research underscores variations in pronunciation, including rhotic and non-rhotic accents; discrepancies in vocabulary, encompassing everyday lexical items; distinctions in spelling; and grammatical preferences regarding tense usage, prepositions, and collective nouns. There is also a focus on stylistic and pragmatic subtleties that affect communication in academic, professional, and casual settings. By examining these distinctions, the study illustrates that British and American English constitute standardized national varieties within a singular language system rather than distinct languages. To communicate effectively across cultures, teach languages, study translation, and do linguistic research, you need to know about these differences. The results add to comparative linguistics by giving a systematic overview of the structural and functional differences between the two main types of English.